Evaluation of Plasma Concentration and Hepatotoxicity of Voriconazole in Pediatric Patients following Hematopoietic Stem Cell Transplantation - Hamidreza Taghvaye Masoumi; Molouk Hadjibabaie; Morvarid Zarif-Yeganeh (Journal of Pharmaceutical Care, 2017)
Background: Invasive fungal infection is one of the most important causes of morbidity and mortality in pediatric patients undergoing Hematopoietic stem cell transplantation (HSCT). Voriconazole as a broad-spectrum anti-fungal agent which has been used widely for prevention and treatment of invasive fungal infections in immunocompromised patients. Alteration in voriconazole plasma concentrations may be resulted in lack of efficacy and some adverse effects.